Isolation and evaluation of the sugarcane UDP-glucose dehydrogenase gene and promoter - Van der Merwe, Jennie (Stellenbosch : University of Stellenbosch, 2008)
Thesis (PhD (Genetics. Plant Biotechnology))--University of Stellenbosch, 2006.